Critical neuroscience meets medical humanities. Issue 1 (7th June 2015) - Slaby, Jan
Abstract : This programmatic theory paper sketches a conceptual framework that might inspire work in critical Medical Humanities. For this purpose, Kaushik Sunder Rajan's account of biocapital is revisited and discussed in relation to the perspective of a critical neuroscience . Critical neuroscience is an encompassing positioning towards the recent public prominence of the brain and brain-related practices, tools and discourses. The proposed analytical scheme has five focal nodes: capital, life, technoscience, (neoliberal) politics and subjectivity. A special emphasis will be placed on contemporary framings of subjectivity, as it is here where deep-reaching entanglements of personhood with scientific practice and discourse, medical and informational technologies, and economic formations are most evident. Notably, the emerging subject position of the 'prospective health consumer' will be discussed as it figures prominently in the terrain between neuroscience and other medico-scientific disciplines.